Saffron: a natural potent antioxidant as a promising anti-obesity drug - Mashmoul, Maryam; Azlan, Azrina; Khaza'ai, Huzwah; Mohd Yusof, Barakatun Nisak; Mohd Noor, Sabariah (MDPI AG, 2013)
Obesity is associated with various diseases, particularly diabetes, hypertension, osteoarthritis and heart disease. Research on possibilities of herbal extracts and isolated compounds from natural products for treating obesity has an upward trend. Saffron (Crocus Sativus L. Iridaceae) is a source of plant polyphenols/carotenoids, used as important spice and food colorant in different parts of the world. It has also been used in traditional medicine for treatment of different types of illnesses since ancient times. Many of these medicinal properties of saffron can be attributed to a number of its compounds such as crocetin, crocins and other substances having strong antioxidant and radical scavenger properties against a variety of radical oxygen species and pro-inflammatory cytokines. The aim of this article is to assess the potential role of saffron and its constituents in the regulation of metabolic functions, which can beneficially alter obesity pathophysiology.